Varieties of Variants of the English Language, Taking into Account the Specifics of Their Pronunciation in Speech on the Example of Local Dialects of the USA, Canada and Australia - Abushaev Amir Kamilevich (Genius Publishing Group, 2022)
Pronunciation is the basic process of expressing the English language. After all, it immediately determines how well you speak or use English. How we pronounce depends largely on practice and where we live. Residents of Australia and the United States speak actively and clearly and express English as it is. Correct pronunciation determines excellent knowledge and skills.
Keywords: Pronunciation; clarity; language barrier; universal language